2018
DOI: 10.7717/peerj.4602
|View full text |Cite
|
Sign up to set email alerts
|

The neglected bee trees: European beech forests as a home for feral honey bee colonies

Abstract: It is a common belief that feral honey bee colonies (Apis mellifera L.) were eradicated in Europe through the loss of habitats, domestication by man and spread of pathogens and parasites. Interestingly, no scientific data are available, neither about the past nor the present status of naturally nesting honeybee colonies. We expected near-natural beech (Fagus sylvatica L.) forests to provide enough suitable nest sites to be a home for feral honey bee colonies in Europe. Here, we made a first assessment of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 79 publications
0
71
1
Order By: Relevance
“…In Europe, the western honeybee Apis mellifera exhibits a dual nature as managed and wild species (Requier et al., ). Despite wild populations of A. mellifera being a threatened component of the native fauna, little attention has been paid to these populations (Kohl & Rutschmann, ; Requier et al., ). Currently, Apis mellifera is classified as 'data deficient' in the IUCN Red List of European bees due to a lack of information on wild populations (De la Rúa et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Europe, the western honeybee Apis mellifera exhibits a dual nature as managed and wild species (Requier et al., ). Despite wild populations of A. mellifera being a threatened component of the native fauna, little attention has been paid to these populations (Kohl & Rutschmann, ; Requier et al., ). Currently, Apis mellifera is classified as 'data deficient' in the IUCN Red List of European bees due to a lack of information on wild populations (De la Rúa et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Honeybee health issues (Potts et al., ) have primarily been discussed with respect to their impact on beekeeping and crop pollination (Potts et al., ), while wild populations are often not considered and even widely assumed as extinct (De la Rúa, Jaffé, Dall ’Olio, Mūnoz, & Serrano, ; Geldmann & González‐Varo, ; Jaffé et al., ; Meixner, Kryger, & Costa, ). Nonetheless, recent studies have shown that wild colonies of A. mellifera can still be found in Europe (Kohl & Rutschmann, ; Oleksa, Gawronski, & Tofilski, ), underpinning the need to increase knowledge on these populations (Alaux, Le Conte, & Decourtye, ; Requier et al., ; Requier & Crewe, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The western honey bee, Apis mellifera L., is the only species of honey bee native to Europe. Its colonies have been harvested since antiquity (Bodenheimer 1951;Crane 1999;Kohl and Rutschmann 2018;Sandklef 1946). Apiculture in the Nordic and neighboring countries has relied for centuries on the domestic honey bee for honey and wax production as well as for pollination (Sandklef 1946;Van Engelsdorp and Meixner 2010;Williams et al 1995).…”
Section: Introductionmentioning
confidence: 99%